Possibilities of driveability and fuel consumption improvement by advanced control power transmission system in passenger car - Bieniek, Andrzej; Jantos, Jerzy; Mamala, Jarosław (Transport, 2007)
The correct work of a power transmission system for the sake of a car motion properties, fuel consumption and pollution emission, requires proper control of an engine and power transmission system. This problem becomes especially significant in the case of automation of the power transmission system and particularly regarding the system of constant gear ratio change between the engine and drive wheels (Continuously Variable Transmission), examined in the paper. This control is based on friction degree conditions estimation between metal belt and the transmission wheels. This paper also describes the experimental results of bench test and road test and applying of different control strategies.First Published Online: 27 Oct 2010